Sclerotium hidrophilum SACC.: Un nuevo hospedante de la micobiota deel arroz en Cuba - Sandoval, I.=700 1 Bonilla, T.; Lopez, M.O.
(Es, En)
Ilus., 6 ref.
Keywords: ORYZA SATIVA; PLANTAS HUESPEDES; SCLEROTIUM; BIOTA; CUBA